Significati e confini del giuridico nella filosofia di Seneca - Zanichelli, Maria (Tesserae iuris, 2023)
In his philosophical works Seneca shows a considerable knowledge of the legal world: he often uses legal terms, he refers to legal institutions and jurisprudential opinions, sometimes he approaches the law from a theoretical perspective. This essay investigates Seneca’s contribution to the philosophy of law and his place in the history of legal thought, highlighting themes such as the relationship between law and imperial power, the limits of the law, the sense of aequum as a normative concept, the natural foundations of man’s duties.